COLLABORATIVE GOVERNANCE DALAM PENANGGULANGAN PENGENDALIAN PENYAKIT VIRUS CORONA KECAMATAN BANTURUNG KABUPATEN BUKIT BATU - Muhamad Yusuf (Majalah Ilmiah Dinamika Administrasi (MIDA), 2022)
Collaborative governance with various parties has become crucial in disaster management. Research into cooperation between non-governmental and governmental entities is becoming crucial to work at this time, when the state is the only single actor capable of carrying out everything is beginning to lose its relevance, so the role of the state must be minimized and must be cut off by the private sector. This research aims to know clearly about Collaborative Governance in the control of coronavirus disease (COVID-19) district Banturung, Bukit Batu district, Palangkaraya City, Province Kalimantan Center. This research uses a type of qualitative research with a descriptive approach and a library search, which is a series of related activities using the Library data collection method. The focus of research was taken using Ansell and Gash in the collaborative governance process, starting with face-to-face dialogue, trust building, commitment to process, shared understanding and temporary results. (intermediate outcome). The research results showed that the collaborative governance process in combating the control of coronavirus disease (COVID-19) goes well through the process of face-to-face dialogue, negotiations carried out well between stakeholders resulted in various activities to combat the spread of control of covid-19. Activities include arrangement, sharing masks, sharing help, and socialization related to Covid-19. The communication process in the collaborative activities of the treatment of the control of covid-19 is carried out with close coordination to carry out the prevention activities, there is socialization, either directly or indirectly.